Analisis Penerimaan Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) di Kabupaten Banjar - Yuliana, Helda; Yunani, Ahmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The transfer of management of Tax for Acquisition of Land and Buildings (BPHTB) and Land and Building Tax–Urban and Rural(PBB-P2) from the central government to regional government is a regional follow-up autonomy and fiscal decentralization policy. With the transfer of BPHTB into local taxes, BPHTB contributed to the District Own Source Revenue(PAD). This research aims to know how much the contribution, how effective and efficient, how BPHTB potency, the obstacles in BPHTB collection, and what strategy needs to be done to increase BPHTB revenue. The type of research is a descriptive method. The data source used is secondary data obtained from Bapenda Banjar district to calculate the contribution, effectiveness, efficiency, and primary data obtained from interviews to know the potential, constraints, and strategies in the revenue of BPHTB. This research can conclude that contribution of BPHTB to local revenue (PAD) is still deficient. The effectiveness of 2012-2016 is beneficial because the point is always above 100%, and the implementation of BPHTB collection is very efficient. BPHTB of Banjar district has a very high potential and potentially will continue to increase. The obstacle faced by the Banjar district government is not yet applied market price and still only refers to NJOP. A strategy that can be done is using price comparison, and Banjar district government routinely conducts an evaluation meeting with BPN and notary/PPAT.